Carer's Attachment Anxiety, Stressful Life-Events and the Risk of Childhood-Onset Type 1 Diabetes - Turin, Anja; Dovč, Klemen; Klemenčič, Simona; Bratina, Nataša; Battelino, Tadej; Lipovšek, Jasna Klara; Uršič, Katarina; Shmueli-Goetz, Yael; Drobnič-Radobuljac, Maja (Frontiers in Psychiatry, 2021)
Background/Objective: Type 1 diabetes (T1D) is among the most common chronic diseases in children/adolescents, the incidence continues to rise worldwide. Different environmental factors have been evaluated in the etiology. In the present study we investigated the role of attachment. We presumed insecure attachment to carers or carers’ own attachment insecurity was related to a higher risk of T1D in children. Methods: We included 101 children with T1D (mean age 11.8 years), 106 healthy controls (11.6 years) and one of their carers. We assessed children’s attachment using the Child Attachment Interview and carers’ attachment using the Relationship Structures Questionnaire. We constructed binary multinomial logistic regression models using attachment to mothers, carers’ attachment representations, and stressful life-events as T1D predictors. Results: Higher carer’s attachment anxiety was associated with the child’s T1D diagnose (p < 0.05; R2 = 0.0613) while security of attachment to mothers showed no significant association. When mothers’ education was included in the model, both attachment anxiety in higher educated mothers and stressful life-events showed a significant association with the child’s T1D (p < 0.001; R2 = 0.293). Conclusions: Our findings suggest that higher attachment-related anxiety in carers with high education and stressful life-events are associated with T1D in children.